Full-Endoscopic Decompression for Congenital Spinal Stenosis Caused by Diastrophic Dysplasia in a 13-year-old Pediatric Patient: A Case Report - Camapum, Emilson (2025)
Introduction: Diastrophic dysplasia (DTD) is a rare disorder that affects the development of cartilage and bone. It is an autosomal recessive skeletal dysplasia that results in short stature with limb shortening, contractures of large joints, spinal deformities, cleft palate, clubfoot, cystic swelling of the external ear, and deformities of the hands. The spine frequently develops excessive lumbar lordosis, cervical and thoracolumbar kyphosis, and scoliosis. Spinal stenosis can also be found, but it is less commonly reported. Case presentation: This study aims to present a case of congenital spinal stenosis caused by DTD causing conus medullaris syndrome in a pediatric patient, which was treated with a full endoscopic bilateral over-the-top interlaminar technique. The patient achieved complete symptomatic recovery without any perioperative complications from the procedure. Conclusion: This is the first report of a full endoscopic decompression for spinal stenosis caused by DTD in the literature. Also, this is the first report of full endoscopic decompression for congenital spinal stenosis in a pediatric patient. Level of evidence IV; Case Series.